PENANAMAN KONSEP IDENTITAS DIRI BERDASARKAN IMAN KRISTEN MELALUI PERANAN PENDIDIKAN KRISTEN - Neri Astriana Koehuan; Dylmoon Hidayat; Chrissya Apitula (Fakultas Keguruan dan Ilmu Pendidikan, 2022)
Knowing identity in the Christian faith is essential to the life of each believer. Understanding the concept of self is closely related to how a person in his daily dealings with him, with others around him and also shows how he represents God. The result of not knowing or knowing yourself wrong can have a bad impact on yourself, others, the environment, as well as faith in God. Thus, the role of Christian education is highly demanded by both Christian education in the family, church and Christian schools to be able to work well together in order to achieve the inculcation of the concept of self-identity according to the Christian faith in children. It is not easy to realize the concept of self-identity in accordance with the Christian faith in the lives of children in an era that is so influenced by the current developments. Therefore, there is a need for awareness from the parties implementing Christian education to instill the principles and values of living according to the Christian faith as a provision for children in navigating their lives to face the challenges of the times.